POTENTIAL ANALYSIS OF HERBAL ACTIVE COMPOUNDS AS IMMUNOTHERAPEUTIC AGENTS AGAINST CLTA-4 RECEPTOR THROUGH IN-SILICO - Zetta, Darlene Nabila; Setiyabudi, Lulu; Issusilaningtyas, Elisa; Indratmoko, Septiana; Aji, Ajeng Puspo (Universitas Muhammadiyah Magelang, 2025)
Immunotherapy is a promising cancer treatment that enhances the body's immune system by targeting immune checkpoint receptors. One of these receptors, CTLA-4, suppresses the activity of T lymphocytes. Several active compounds derived from herbs, including astragaloside IV, flindersine, n-butylidenephthalide, and xanthorrhizol, have demonstrated potential in anticancer immunotherapy. The objective of this study is to investigate the interaction between these active compounds and the CTLA-4 receptor using molecular docking simulation. This experimental research was conducted from January – June 2023 in the pharmaceutical chemistry laboratory at Al-Irsyad Cilacap University with methods including ligand and receptor preparation, blind molecular docking, RMSD validation, and visualization of the structure. Our findings indicate that all four active compounds can interact with the CTLA-4 receptor and inhibit it with bond energies of astragaloside IV -7.3, flindersine -5.7, n-butylidenephthalide -5.0, and xanthorrhizol -4.9, at RMSD 0. However, the interaction does not involve the same amino acid residues as the comparator ligand ipilimumab due to differences in bond area.